Sans Patrie, le livre oublié de Johanna Spyri qui annonce Heidi - Jean-Michel Wissmer (Strenae)
This article analyzes a little-known novel by Johanna Spyri, Heimatlos: Two stories for children, and for those who love children, which was recently republished in France. Among the works by the author of Heidi, Heimatlos is an exception: this novel seems to be both a template of Heidi as well as a kind of "Heidi in reverse."